(untitled) (Indian Journal of Public Health Research & Development, 2025)
Background & objectives : Pancytopenia may be a manifestation of wide variety of disorders which primarily or secondarily affects the bone marrow. Bone marrow aspiration is a minimally invasive , out – patient procedure which provides definitive diagnosis in cases of pancytopenia. The present study was conducted to analyse the various causes of pancytopenia by evaluating bone marrow aspiration and to correlate bone marrow aspiration findings with clinical presentation, complete blood counts and peripheral blood picture. Methods : This prospective study was conducted in the Department of Pathology , Muzaffarnagar Medical College for a period of 12 months . Total 60 cases were evaluated for pancytopenia. Results : Out of 60 cases, 25 (41.7%) cases were females and 35 (58.3%) were males with slight male preponderance . Maximum number of cases were in the age group of 31 - 40 years. Most common cause of pancytopenia was megaloblastic anaemia followed by hypoplastic marrow , iron deficiency anaemia , nutritional deficiency and others. Interpretation & Conclusion: Along with detailed clinical examination and complete blood count , bone marrow examination is still the indispensable diagnostic modality to diagnose the aetiology of pancytopenia.